Rancang Bangun Sistem Kehadiran Pegawai Berbasis Web (Studi Kasus: Yayasan Cahaya Pelangi Indonesia) - Rifki Purna Irawan Isa Rifki; Tri Hidayati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The presence of employees is a major factor in an agency in achieving its goals. This is related to the discipline of an employee and has an impact on the good and bad management of an agency, the impact obtained is in the form of a lack of production produced by a company. This also has a bad impact on the income of a company. At the Cahaya Pelangi Indonesia Foundation, the system used in the attendance process is still manually using a daily attendance book which has an impact on the efficiency and effectiveness of data collection, data search as well as data recap calculations which take a long time. In addition there are also risks that may occur such as errors or loss of attendance data. This can be detrimental to a company. Based on the problems above, a Web-Based Employee Attendance System was created at the Cahaya Pelangi Indonesia Foundation. The research method is the method used in data collection which includes direct interview research and literature. The method used for software development is the waterfall method which includes: System requirements analysis, design, coding, testing and implementation. With the resulting web-based employee attendance application, it can provide convenience in the attendance process, search data, and minimize employee fraud in conducting attendance and minimize loss of attendance data at the Cahaya Pelangi Indonesia Foundation.